Análisis de las lesiones histopatológicas en hígado y riñón en porcinos y bovinos faenados en el camal municipal de Guaranda - Santillán Santillán, Ángel Manuel (2025)
The study aimed to analyze histopathological lesions in the liver and kidney of pigs and cattle slaughtered at the Guaranda municipal slaughterhouse. The study followed a non-experimental, descriptive, and cross-sectional design. It was an observational analysis in which no variables were manipulated, but lesions present in the viscera at the time of evaluation were documented. Comparisons between groups were performed through frequency and proportion analysis, with no intervention in the conditions of origin of the organs. The biological material studied consisted of a total of 64 organs, distributed as follows: 16 livers and 16 kidneys from pigs, and 16 livers and 16 kidneys from cattle. These viscera were collected during routine slaughtering for macroscopic and histopathological analysis. Histological processing was performed in an accredited laboratory, and the data obtained were organized, classified, and analyzed with scientific rigor to ensure the validity and reliability of the results. Therefore, it was determined that the most frequent histopathological lesions in the liver and kidney of cattle and pigs slaughtered at the Guaranda Municipal Slaughterhouse were lymphoplasmacytic inflammation, periportal fibrosis, and lymphoplasmacytic interstitial nephritis. Females and adult animals showed a greater frequency and diversity of lesions, especially in the liver. A total economic loss of $33.20 was also estimated due to the confiscation of 15 viscera with serious lesions. Finally, it was concluded that visceral lesions in cattle and pigs reflect chronic health problems, affect adults more frequently, and generate economic losses that can be avoided through prevention and control at source.